2022
DOI: 10.3389/fenrg.2022.840140
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability Metrics of Photoelectrochemical Water Splitting

Abstract: Photoelectrochemical (PEC) water splitting, one of the most promising technologies for clean hydrogen generation, has drawn considerable attention over the past few decades. Achieving simultaneous highly efficient and stable unassisted PEC water splitting has been the “holy grail” in clean and renewable fuel generation. State-of-the-art photoelectrodes have shown relatively high efficiencies (∼10–20%). Still, their stability is limited due to photoelectrode chemical instability, electrolyte resistance, mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…A procedure for measurement of long-term stability based on chronoamperometric measurements in PEC systems was only recently proposed by Vanka et al based on their studies on Pt-decorated GaN nanostructures on an n + -p Si photocathode 38,39 and extended by Zhang et al, who suggested to rely on in operando dissolution measurements for thicker photoabsorbers. 40 Even though over the past decade the call for standards regarding stability testing has increased and research about degradation of photocatalysts has intensied, 38 the topic of degradation in photocatalytic and PEC systems still remains a considerable challenge to overcome. An in-depth understanding of degradation processes is necessary to nd solutions to prolong the lifetime of photocatalysts in water splitting applications and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…A procedure for measurement of long-term stability based on chronoamperometric measurements in PEC systems was only recently proposed by Vanka et al based on their studies on Pt-decorated GaN nanostructures on an n + -p Si photocathode 38,39 and extended by Zhang et al, who suggested to rely on in operando dissolution measurements for thicker photoabsorbers. 40 Even though over the past decade the call for standards regarding stability testing has increased and research about degradation of photocatalysts has intensied, 38 the topic of degradation in photocatalytic and PEC systems still remains a considerable challenge to overcome. An in-depth understanding of degradation processes is necessary to nd solutions to prolong the lifetime of photocatalysts in water splitting applications and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuel-based traditional energy sources such as natural gases, coal, and gasoline fulfilled the energy demands of human beings for long decades. Such unlimited use has not only led to a depletion of these natural resources but also raised the global average temperatures through the global warming phenomena, environmental degradation, etc. , Hence, for the sustainable development of human society, it is important to discover alternatives and renewable energy sources. , Recently, hydrogen generation by photoelectrochemical (PEC) water splitting has become an attractive field for research as it promises to clean and green energy production without any undesirable byproducts. PEC water splitting is a viable and environment-friendly solution to generate an alternative source of energy with the minimization of global warming. After the discovery of water splitting in a TiO 2 single crystal, , various metal oxides such as WO 3 , Cu 2 O, SnO 2 , Fe 2 O 3 , BiVO 4 , and ZnO; a few metal nitrides such as Ta 3 N 5 , Ni 3 N, and TiN; and metal sulfides such as ZnS, CdS, NiS, etc., have been investigated for PEC water splitting. However, each semiconductor has its advantages and disadvantages concerning its large band gaps with low efficiency, earth abundance, toxicity, stability, and fabrication cost. Therefore, to enhance the PEC efficiency and transform the technology at commercial platforms, novel material combinations, architectures, and configurations are being extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, research efforts have mostly focused on improving the activity of PEC materials. Campaigns mapping their long‐term stability and efforts to standardize durability tests have only been initiated recently [20] . Especially for hybrid systems with molecular catalysts, detailed degradation studies are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Campaigns mapping their long-term stability and efforts to standardize durability tests have only been initiated recently. [20] Especially for hybrid systems with molecular catalysts, detailed degradation studies are scarce. Traditional postmortem analysis based on physicochemical characterizations only reveal a before/after comparison but does not reveal any details about transformations of the photoelectrode during specific PEC operations.…”
Section: Introductionmentioning
confidence: 99%